Gender Approaches in the Translation Classroom Training the Doers - De Marco, Marcella; Toto, Piero (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
'A rigorous and illuminating guide for language scholars, trainers and students who want to experience a gender-oriented perspective and awareness on translation theory and practice.' - Annarita Taronna, University of Bari Aldo Moro, Italy This volume examines strategies for embedding gender awareness within translation studies and translator training programmes. Drawing on a rich collection of theoretically-informed case studies, its authors provide practical advice and examples on implementing gender-inclusive approaches and language strategies in the classroom. It focuses on topics including, how to develop gender-inclusive practices to challenge students' attitudes and behaviours; whether there are institutional constraints that prevent trainers from implementing non-heteronormative practices in their teaching; and how gender awareness can become an everyday mode of expression. Positioned at the lively interface of gender and translation studies,this work will be of interest to practitioners and scholars from across the fields of linguistics, education, sociology and cultural studies. Marcella De Marco is a Senior Lecturer in Translation at London Metropolitan University, UK. She is the author of Audiovisual Translation through a Gender Lens (2012). Piero Toto is a Senior Lecturer in Translation at London Metropolitan University, UK. His research interests include translation technology, localization, gender and queer studies.